Impact of modified atmosphere packaging on the microbiological and physicochemical analyses of mirror carp (Cyprinus Carpio L., 1758) fish balls - Doğan, E; Beyazgül, P; Arslan, A (Journal of the Hellenic Veterinary Medical Society, 2025)
In this study, the impacts of dissimilar modified atmosphere packaging treatments on the microbiological and physicochemical quality of mirror carp fishballs were investigated. In the study, one control group (K: under air) and three experimental groups (D1: 55% CO2 + 15% O2 + 30% N2, D2: 65% CO2 + 10% O2 + 25% N2, D3: 75% CO2 + 10% O2 + 15% N2) consisted of fishball samples which prepared from fillets of mirror carp of caught fresh. The fishballs for these groups were prepared using fillets from freshly caught mirror carp. After undergoing the respective MAP treatments, the cheese samples were stored at 4°C. Evaluations of their quality were carried out on storage days 0, 3, 6, 9, 12, 15, and 18. During the storage period, the D2 and D3 groups exhibited lower counts of Enterobacteriaceae, coliform bacteria, and yeast-mold in comparison to other groups (P≤0.05). The levels of total volatile base nitrogen and the thiobarbituric acid index witnessed a progressive rise across all groups, with discernible differences noted among them (P≤0.05). Sensory evaluation outcomes divulged that the shelf life of fishballs extended to 9 days for the control group, 15 days for the D1 group, and 18 days for both the D2 and D3 groups (P≤0.05). Based on these conclusions, it can be inferred that fishballs subjected to high CO2 MAP have a notably prolonged shelf life when stored under refrigeration.